Adolescent-Friendly Remedies for the Challenges of Focus Group Research. (September 2013) - Daley, Alison Moriarty
Focus groups are an increasingly popular method of qualitative research; however, as with any research method, limitations emerge that were not anticipated. This article reviewed the limitations reported in 21 research studies, published between 2002 and 2012, to identify the common concerns of researchers in focus group studies with adolescents. Limitations focused on methodological concerns, recruitment challenges, and the potential influences of peers and the moderator on research results. Remedies are suggested for modifying the focus group method to address these potential challenges within the context of adolescent development and adolescent-friendly care.